Lambdoma Matrix Harmonic Music Therapy for Elderly Female Insomnias in Taiwan: A Preliminary Evaluation of this Body, Mind and Soul Music Therapy - Lin, Jyh-Woei (European Journal of Applied Sciences, 2024)
The 2 Music Therapies are used for the elderly female insomnias of 2 groups because insomnia is one of the major problems of menopausal women with growing age. Each group has 21 insomnias. The Lambdoma Matrix Harmonic Music (LMHM) and Medical Resonance Therapy Music (MRTM) therapies own around 57% of success rate and around 52% of success rate, respective. Therefore, the LMHM can recognize as the good therapy music to improve the quality of sleeping.